THE EFFICACY OF WAVEONE GOLD AND MTWO RETREATMENT FILES IN THE REMOVAL OF CARRIER-BASED GUTTA-PERCHA OBTURATORS - Ramona Mărușter; Luminița-Maria Nica; Camelia Gruia; Roxana-Maria; Laura-Elena Cîrligeriu (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study To compare the efficiency of two rotary nickel-titanium (NiTi) systems: MTwo Retreatment (VDW GmbH, München, Germany) and WaveOne Gold (Dentsply Maillefer, Ballaigues, Switzerland) in the removal of two different carrier-based gutta-percha (GP) obturators. Material and methods 12 plastic blocks with simulated root canals were shaped, cleaned and obturated: 6 with GuttaCore® (Dentsply Maillefer) and 6 with GUTTAFUSION® (VDW). After one week, each group was divided into two subgroups and WaveOne Gold (WOG) and MTwo R (MTR) were used in the removal of GP from 3 samples of each carrier type. The time was recorded, photographs were taken and scores for remaining gutta-percha were atributed at the end of retratment. The area of each retreated canal was compared with the total area of the resin block. Results In a similar amount of time, the WOG files were able to remove a higher amount of GP than MTwo R, without significant alteration of the root canal shape. Conclusions Neither of the files could remove entire amount of GP, but WOG proved to be more efficient.